2019
DOI: 10.5551/jat.48314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardio–Ankle Vascular Index (CAVI) and CAVI<sub>0</sub> in Large Healthy and Hypertensive Populations

Abstract: Original ArticleAim: The cardio-ankle vascular index (CAVI) represents the blood pressure-independent arterial stiffness from the origin of the aorta to the ankle. CAVI0 has been proposed as a variant index. We aimed to clarify the difference between CAVI and CAVI0 among large populations, and to explore reasons of the difference. Methods:The subjects were 5,293 Japanese healthy and 3,338 hypertensive people. Simple and multiple regression analyses were performed using age, sex, body mass index, systolic, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0
8

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 40 publications
2
48
0
8
Order By: Relevance
“…Recent studies showed that arterial stiffness has attracted attention as a potentially useful parameter for risk stratification of patients with ACS 3 , 4 ) . Cardio-ankle vascular stiffness index (CAVI) is a noninvasive measure of arterial stiffness that is not influenced by blood pressure at the time of examination 5 , 6 ) . We previously reported that high CAVI was an independent predictor of cardiovascular (CV) events and nonfatal ischemic stroke in patients with ACS 3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that arterial stiffness has attracted attention as a potentially useful parameter for risk stratification of patients with ACS 3 , 4 ) . Cardio-ankle vascular stiffness index (CAVI) is a noninvasive measure of arterial stiffness that is not influenced by blood pressure at the time of examination 5 , 6 ) . We previously reported that high CAVI was an independent predictor of cardiovascular (CV) events and nonfatal ischemic stroke in patients with ACS 3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Another difference between CAVI and CAVI 0 is the use of P 0 in the formula of CAVI 0 . Although Spronck et al [3] claimed that the new formula of CAVI 0 is independent of blood pressure, in a large study on 5293 individuals, Shirai et al [5] recently showed that CAVI 0 is not accurate because of its strong dependency on P d . Another reason that CAVI 0 provides equivocal results is that Spronck et al [3] did not take into account the physiological properties of individuals, such as their body mass index (BMI).…”
mentioning
confidence: 99%
“…In a recent study, Shirai et al compared CAVI and CAVI 0 in a large population of normotensive and hypertensive individuals [9]. While the use of large populations should be greatly applauded, all analyses presented in their study are cross-sectional, that is, in each individual, CAVI/CAVI 0 was measured only once.…”
mentioning
confidence: 99%
“…Alizargar et al point out that Shirai et al observed a negative, "inexplicable" correlation between CAVI 0 and diastolic blood pressure (DBP) in healthy individuals, which Shirai et al then used as a reason to label CAVI 0 as "inappropriate" [1,9]. Again, this correlation is cross-sectional, and indicates (statistically) that subjects with a higher CAVI 0 on average have a lower DBP.…”
mentioning
confidence: 99%